A tale of refugees : Rohingyas in Bangladesh - Razzaq, Abdur; Haque, Mahfuzul; Centre for Human Rights (Dhaka, Bangladesh) (Dhaka : Centre for Human Rights, 1995)
On Rohingyas of Arakan State, Burma taking refuge in Bangladesh, and their repatriation.
Includes bibliographical references.
Keywords: Rohingya (Burmese people); Rohingya (Burmese people) -- Bangladesh; Refugees -- Burma; Refugees -- Bangladesh